The Histological Spectrum and Clinical Significance of T Cell–mediated Rejection of Kidney Allografts. Issue 5 (19th December 2022) - Filippone, Edward J.; Farber, John L.
Abstract : T cell–mediated rejection (TCMR) remains a significant cause of long-term kidney allograft loss, either indirectly through induction of donor-specific anti-HLA alloantibodies or directly through chronic active TCMR. Whether found by indication or protocol biopsy, Banff defined acute TCMR should be treated with antirejection therapy and maximized maintenance immunosuppression. Neither isolated interstitial inflammation in the absence of tubulitis nor isolated tubulitis in the absence of interstitial inflammation results in adverse outcomes, and neither requires antirejection treatment. RNA gene expression analysis of biopsy material may supplement conventional histology, especially in ambiguous cases. Lesser degrees of tubular and interstitial inflammation (Banff borderline) may portend adverse outcomes and should be treated when found on an indication biopsy. Borderline lesions on protocol biopsies may resolve spontaneously but require close follow-up if untreated. Following antirejection therapy of acute TCMR, surveillance protocol biopsies should be considered. Minimally invasive blood-borne assays (donor-derived cell-free DNA and gene expression profiling) are being increasingly studied as a means of following stable patients in lieu of biopsy. The clinical benefit and cost-effectiveness require confirmation in randomized controlled trials. Treatment of acute TCMR is not standardized but involves bolus corticosteroids with lymphocyte depleting antibodies for severe, refractory, or relapsing cases. Arteritis may be found with acute TCMR, active antibody-mediated rejection, or mixed rejections and should be treated accordingly. The optimal treatment ofchronic active TCMR is uncertain. Randomized controlled trials are necessary to optimally define therapy.